Notes on a Gladiatorial Inscription from Plotinopolis - Papanikolaou, Dimitrios (Tekmeria, 2019)
The paper is concerned with a new gladiatorial tombstone from Plotinopolis. The paper raises serious doubts on the text of the inscription offered by itsinitial editor (Tsoka 2015); it also pinpoints towards Sharankov’s proposal(Année Épigraphique 2014 [2017] no. 1165, 493) as the only viable solution forthe text of the inscription, citing also unnoticed parallel passages from ancientGreek inscriptions and texts as evidence substantiating the new reading of the stone (see nn. 7-9). The paper expresses also disagreement over Tsoka’s assertion that thewords λοῦδοι and Μάτερνος of the inscription are mere transcriptions into Greek letters of the Latin words ludi, Maternus – and that the name Μάτερνοςimplies Romanisation. It is argued that the Latin-derived name of a gladiator ghting in the Eastern (Greek-speaking) side of the Roman Empire is not a safe marker of Romanisation. This is demonstrated by the epigraphical evidenceattesting to the habit of Greek-speaking gladiators to adopt professionalpseudonyms, many of them (25% of all recorded cases) Latin-derived ones; thepaper argues that the name Μάτερνος is simply a Latin-derived gladiatorialpseudonym. Plutarch’s testimony further substantiates that gladiators could be ethnic Greeks or culture-Greeks (see n. 20). As far as the word λοῦδοι is concerned, the poetic declination of the word in the stone attests to the laststages in the adaptation of a Latin-derived word into a fundamentally Greek linguistic environment. The paper argues that the Latin-derived vocabulary ofthe stone (Μάτερνος, λοῦδοι) should be viewed as a further piece of evidenceattesting to the recognition on the part of the Greek-speakers of the time, that gladiation was a fundamentally Roman cultural institution, a cultural import whose onomastics and terminology could rather remain untranslated.